The relationship between knowledge search strategies and absorptive capacity: A deeper look. (August 2016) - Ferreras-Méndez, José Luis; Fernández-Mesa, Anabel; Alegre, Joaquín
Abstract: The present study analyzes how the breadth and depth of search strategies affect the dimensions of a firm's absorptive capacity: exploration, transformation and exploitation. Results of an analysis of a sample of 467 Spanish manufacturing firms reveal that openness of external knowledge search contributes to firms' exploratory, transformative and exploitative learning processes in different ways. In particular, a strong curvilinear effect of external knowledge search breadth on exploratory and exploitative learning was found. It is also important to establish deep relationships with external agents to achieve transformative and exploitative learning up to a certain point after which relationships become negative. Interestingly, for a firm to develop explorative learning, it is not important to establish deep relationships. And for a firm to develop transformative learning it is not important to establish broad relationships. Some suggestions for managers and future lines of research are provided. Highlights: The present study analyses how different knowledge search strategies affects absorptive capacity's learning processes. The analysis is performed on a sample of 467 Spanish manufacturing firms. Strong curvilinear effect exists between breadth of external knowledge search and exploratory and exploitative learning. Sustaining deep relationships contribute to transformative and exploitative learning up to a point after which become negative.